Edukasi pada Pasien dan Keluarga tentang Penerapan Keselamatan Pasien di RSUD Arifin Achmad Provinsi Riau - Lastari, Raja Fitrina; Lita, Lita; Sari, Siska Mayang; Nur’afifi, Nur’afifi (Universitas Baiturrahim, 2025)
The quality of health services can lead to a level of patient satisfaction that comes from relatively specific factors, one of which is by implementing patient safety targets. Ensuring patient safety will have an impact on the minimisation of nosocomial infections, the time and cost of care incurred by patients will be reduced. This will have an effect on increasing patient satisfaction with the health services received. Patient safety education is a key component in efforts to improve the quality of health services and prevent patient safety incidents. The purpose of this community service is to provide an understanding of the application of patient safety using the lecture method of distributing Flyers, leaflets containing knowledge about the application of patient safety. Activities were carried out on Friday, 20 September 2024, by contracting with patients early. The activity begins with giving a questionnaire (Pre test), then counselling is given to patients with the aim of getting an overview of patient knowledge about patient safety and then given a questionnaire (Post test) to patients with the aim of evaluating patient knowledge from what has been explained. It is hoped that after being given counselling, patients can understand the important role of understanding patient safety and understand their involvement in services. An integrated and sustainable educational approach can help create a culture of patient safety.